Longest gallbladder: A case report. (2017) - Yadav, Rahul; Kankaria, Jeevan
Highlights: Longest gallbladder (30 cm), documented till date, removed successfully. Mucocele of gallbladder operated without any complications through standard 4 port technique. Abstract: Introduction: A gallbladder mucocele is the distention of the gallbladder by an inappropriate accumulation of mucus. Decreased bile flow, decreased gallbladder motility, and altered absorption of water from the gallbladder lumen are predisposing factors to biliary sludge. However, it is more likely to be a small part of a complex disease process involving inflammation of the gallbladder wall and changes to the lining of the gallbladder changing the consistency of its secretions. We would like to present a case of mucocele gallbladder operated successfully by laparoscopic cholecystectomy. Case report: Herein, we present a case of 46 year old female presenting with symptoms of pain in right hypochondrium with ultrasonographic diagnosis of cholelithiasis undergone successful laparoscopic cholecystectomy with Intraoperative findings of: 1. The length of the gallbladder was measured to be 30 cm. 2. A large stone was impacted at the neck of gallbladder, which was leading to mucocele formation. Conclusion: Mucocele of gallbladder present an important hurdle in successful laparoscopic cholecystectomy. A habit of calm and slow dissection with precautions should be developed. Clearance of the calot's triangle with limited use of electro cautery should be done before proceeding towards ligation or clip application to various structures.